Modelling of heat stress in a robotic dairy farm. Part 1: Thermal comfort indices as the indicators of production loss. (November 2020) - Ji, Boyu; Banhazi, Thomas; Ghahramani, Afshin; Bowtell, Les; Wang, Chaoyuan; Li, Baoming
Abstract : Thermal comfort indices (TCIs) have been developed to assess heat stress and model the relationship between thermal parameters (e.g. dry-bulb temperature) and animal responses (e.g. daily milk yield, DMY). The published models typically include temperature humidity index (THI), black globe humidity index, environmental stress index, equivalent temperature index, heat load index, respiration rate index and comprehensive climate index. This study was conducted to compare the performance of these published TCIs using data collected from a robotic farm situated in a subtropical climate region. The comparison also included models formulated between basic thermal parameters and animal responses (DMY and milk temperature (MT)). The statistical analyses found dry-bulb temperature can provide a similar level of performance to other TCIs in assessing heat stress. The spatial variability between on-farm measurements and the local weather station can be neglected when modelling with TCIs and MT. For cows with an average DMY of 31 kg cow −1 d −1, the threshold for significant decline of DMY was reported as THI >64 (P < 0.05). The daily minimum TCIs were found to be highly correlated with production loss, indicating that sufficient night-time cooling was important for preventing production losses. The potential of implementing a simplified assessment of heat stress using an on-line dataset was also demonstrated by this study. Highlights: Performance evaluation of published TCIs and basic thermal indicators. Test the consistency of using on-farm microclimate and regional climate data. THI-64 was found as the start of heat stress for cows with 31 kg·cow −1 ·d −1 DMY. Importance of night-time cooling to relief heat stress was demonstrated.